Alpha Cell Stimulus-Secretion Coupling and Intercellular Interactions in Health and Type 2 Diabetes: Sklopitev med stimulacijo in sekrecijo in medcelične interakcije celic alfa v zdravju in pri sladkorni bolezni tipa 2 - Pohorec, Viljem; Zadravec, Nika; Turk, Marko; Dolenšek, Jurij; Stožer, Andraž (Acta Medico-Biotechnica, 2023)
Beta cell dysfunction has long been thought to be at the root of type 2 diabetes pathogenesis; however, a bi-hormonal model of the disease appears to be more realistic. Alpha cells play a significant role in glucose homeostasis due to their communication with other cells within the islets of Langerhans and tissues like the liver through glucagon action. Although a concise model of their physiology is still lacking, new approaches provide more insight into the pathways of glucagon secretion and processes regulating it, which gives insight into alpha cell function in health and disease, with potential implications for type 2 diabetes management.
Keywords: Alpha cell, calcium imaging, epinephrine, physiology, type 2 diabetes mellitus